GAMBARAN PRAKTIK PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI ) PADA ANAK USIA 12-24 BULAN - Gusmeldawati Gusmeldawati; Jumaini Jumaini; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Introduction: Complementary breastfeeding is a very important nutrient in supporting the development and nutritional growth of children. This study aims to identify the practice of complementary feeding based on WHO recommendations which include the timeliness of giving, adequacy, safety, and active and feeding responsive. Methods: This study used a descriptive quantitative design with the number of 75 respondents of mothers who have children aged 12-24 months using purposive sampling technique. The measuring instrument used is a questionnaire sheet. The analysis used is descriptive. Results: The results showed that the mother's age was 26-35 years old as many as 32 people (42.7%), 30 people (40.0%) Senior High School, 63 people (84.0%) did not have a job/housewive, respondent's family income less than minimum wage was 65 people (86.7%), parity of primiparous respondents was 43 people (57.3%). The timeliness of giving category was 40 people (53.3%), the adequacy of the good category was 45 people (60.0%), the safety category was good as many as 39 people (52.0%), active feeding and responsive good categories were 49 people (65.3%), and overall the practice of complementary feeding to children aged 12-24 months in the right category was 42 people (56.0%).Conclusion: The results of this study can be an information or knowledge for the community and become promotional data for health workers in carrying out health education about the practice of complementary feeding. Keywords: complementary feeding, practice of giving,